2018
DOI: 10.1128/jvi.01345-17
|View full text |Cite
|
Sign up to set email alerts
|

VP1 and VP3 Are Required and Sufficient for Translation Initiation of Uncapped Infectious Bursal Disease Virus Genomic Double-Stranded RNA

Abstract: Infectious bursal disease virus (IBDV) is a bi-segmented double-strand RNA (dsRNA) virus of the family. While IBDV genomic dsRNA lacks a 5' cap, the means by which the uncapped IBDV genomic RNA is translated effectively is unknown. In this study, we describe a cap-independent pathway of translation initiation of IBDV uncapped RNA that relies on VP1 and VP3. We show that neither purified IBDV genomic dsRNA nor the uncapped viral plus-sense RNA transcripts was directly translated and rescued into infectious viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 50 publications
(59 reference statements)
2
32
1
Order By: Relevance
“…Viral VP3 is a multifunctional "scaffold" protein and plays important roles in the virus life cycle [20,22,29,38]. Thus, it is identified as a potential target to disrupt virus-host interactions [30,31,39].…”
Section: Host Proteins Immunoprecipitated With Vvibdv Vp3mentioning
confidence: 99%
See 1 more Smart Citation
“…Viral VP3 is a multifunctional "scaffold" protein and plays important roles in the virus life cycle [20,22,29,38]. Thus, it is identified as a potential target to disrupt virus-host interactions [30,31,39].…”
Section: Host Proteins Immunoprecipitated With Vvibdv Vp3mentioning
confidence: 99%
“…Interactions between pVP2 and VP3 drive capsid assembly [26][27][28]. Recently, it has been reported that both VP3 and VP1 are required to translation initiation of uncapped viral dsRNA [29]. VP3 also interacts with host factors to modulate viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…IBDV dsRNA pulldown assay IBDV genomic dsRNA extraction was performed as previously described (12,40), and the purified IBDV genomic dsRNA was conjugated with biotin by UV irradiation (365 nm) as previously described (41). Biotin-labeled IBDV dsRNA was either added to whole cell lysates or incubated with E. coli-produced recombinant His-chSTAU1/(1-468).…”
Section: Preparation Of Chstau1/(1-468) In Escherichia Colimentioning
confidence: 99%
“…VP3 interacts both with VP1 and viral dsRNA to assemble into RNP complexes (9,10) in which it significantly stimulates the VP1 RdRp activity (11). Furthermore, both VP1 and VP3 are required and sufficient for the translation initiation of IBDV uncapped genomic dsRNA (12).…”
mentioning
confidence: 99%
“…The RNP complex is also involved in intracellular viral replication and translation (26), during which VP3 significantly stimulates the VP1 RdRp activity (27). Moreover, VP1 and VP3 have been identified to be the minimal set of trans-acting factors needed to render the infectivity to IBDV genomic dsRNA (28). In addition, both VP3 and VP4 are considered to be antagonists of interferon-␤ induction (28)(29)(30)(31), and VP3 has also been suggested to act as an antiapoptotic protein that prevents the activation of the cellular dsRNA-dependent protein kinase R (32,33).…”
mentioning
confidence: 99%